Rumour: A Lexicographical Description of the Word Meaning From Evidentiality Perspective - S. V. Ivanova; G. Sh. Khakimova (Дискурс профессиональной коммуникации, 2024)
Current media studies as well as the analysis of social interaction put forward the notion of rumours playing a significant role in human communication and making it a full-fledged object of linguistic analysis. The article is devoted to the description and unification of the lexicographical meaning of the word ‘rumour’ which is basic for indirect knowledge transmission. The proposed research perspective is preconditioned by the interest in uncertain knowledge and informal communication practices including such phenomena as rumors, gossip, etc., inherent in professional communication, as well as in the category of evidentiality. The empirical material comprises dictionary interpretations, the inconsistency of which stipulated the application of the ideas of lexical semantics. Componential analysis is chosen as the main method to define meanings. As a result, the polysemy of the word under study has been exposed, with its structure including five lexico-semantic variants with different types of relations. The invariant set of ‘without confirmation’, ‘uncertain origin’, ‘questionable accuracy’ components in the structure of the meanings indicates that there is a direct connection of the word semantics with the linguistic categories of evidentiality and epistemic modality. The analysis shows that when interpreting the values obtained, the concept of evidence as a source of information has an explanatory potential, the crucial factor being its distinct classification in terms of levels. The extensive typology of reportive evidentials enables to define the central meaning of the word ‘rumour’ as information characterized as transmitted knowledge, realized through informal statements, categorized as a proper reportative marked by the third level of evidence. The core ‘questionable accuracy’ seme testifies to the correlation of the reportative evidential value and the epistemic evaluation of the acquired knowledge which manifests itself in the fact that indirect mediated access to information potentiates its qualification as lacking confirmation.